Say it right: public speaking for future leaders at SMK Three Rivers - Robert, Cindy; Jeri, Shirley Clare; Daneil, Imelia Laura; Bohari, Mohamad Musa; Kamaruddin, Siti Faridah (Corporate Communication Unit, UiTM Mukah Campus, 2025)
The workshop aimed to equip secondary school students with confidence in communication, presentation skills, and English literacy through interactive activities. Thirty Form Four students participated, guided by Miss Shirley Clare, the main speaker for the day. The session combined lively games with structured learning, encouraging students to work in groups to prepare and deliver short presentations. With templates and facilitator support, participants were able to organise their ideas effectively.